Sostenibilidad financiera del sector asociativo del cantón Loja - Coronel Macas, Carlos Michael (2023)
The challenges of financial sustainability are particularly important for non-profit organizations, since they serve vulnerable populations with great needs and low income. The present research was developed with the general objective of analyzing the financial sustainability of the associative sector of the Popular and Solidarity Economy (EPS) in Loja canton and to learn how the organizations maintain their activities. The methodology used provided the intellectual basis on which the research was built; the objectives were developed based on methods, materials and instruments. The data that was analyzed belong to the Loja canton period 2017-2021, the information analyzed in the study is of longitudinal cut with mixed approach. For which a descriptive type of research was conducted where the associations of the sector were characterized and correlational to identify in the framework of financial sustainability which variables are related to such sustainability, evaluated through the profitability variable (ROA and ROE). Among the most outstanding results, a prolonged growth of both organizations and partners was observed from 2017 to 2021; however, a considerable gap between the groups of associations was evidenced, with a low participation of consumer associations compared to the other groups. In addition, it was shown that members with a bachelor's degree have a greater participation in the associative sector and the seniority range with the highest representation of members are those with between 1 and 3 years of seniority. Using Spearman's correlation coefficient, the degree of relationship between the variables was examined and it was verified that there is no relationship between the variables compared, finding an independence between sustainability (ROA and ROE) and the financial indicators. It is concluded that the organizations of the associative sector are considered as moderately sustainable associations that have been experiencing a growth process of 28%, and are fundamental not only for the permanence of the popular and solidarity economy, but also for the economy at the national level.